2003
DOI: 10.1093/jjco/hyg092
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors Affecting the Outcome of Nasopharyngeal Carcinoma

Abstract: High locoregional control for nasopharyngeal carcinoma was achieved with multisegmental intensity-modulated radiotherapy. Distant metastases are still the main impact on survival. More effective chemotherapy regimens and other systemic agents are needed to decrease the rate of distant metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
68
2
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 35 publications
9
68
2
2
Order By: Relevance
“…Although the differences between node stage and sex subgroups in terms of OS were not statistically significant, trends toward significance were observed. These findings are consistent with results of most other studies (4,10,14). In conclusion, our study provides some evidence on the outcome of Iranian patients with nasopharyngeal cancer and factors influencing it.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although the differences between node stage and sex subgroups in terms of OS were not statistically significant, trends toward significance were observed. These findings are consistent with results of most other studies (4,10,14). In conclusion, our study provides some evidence on the outcome of Iranian patients with nasopharyngeal cancer and factors influencing it.…”
Section: Discussionsupporting
confidence: 93%
“…Liu et al evaluated 83 patients with non-metastatic nasopharyngeal carcinoma treated with intensity modulated radiation therapy (IMRT) with or without chemotherapy and analyzed the factors influencing their outcome. Three-year OS of the patients was 82% and stage of disease, N-classification and cumulative dose to primary tumor were significant prognostic factors for overall survival (10). In another study in China, Wang et al showed three-year overall survivals of 83% and 88% among Uyghur and Han patients, respectively.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover this issue is complicated by the fact that the radiation dose required to eradicate tumor from nasopharynx are far more than what is considered to be the tolerance limit of surrounding normal structures (Liu et al, 2003). To address these challenges 2 dimensional radiotherapy techniques, that has been used traditionally, was replaced by three dimensional conformal radiotherapy (3DCRT) (Teo et al, 2004).…”
Section: Plan Dose Evaluation Of Three Dimensional Conformal Radiothementioning
confidence: 99%
“…The 5-year OS rate of all 53 patients was 25.5%, and the 5-year OS rate of the 24 patients treated by IMRT was 45.5%. These rates were significantly decreased compared with the OS rate of patients with local advanced NPC (T3-T4) (2,3,(11)(12)(13)(14)(15). Previous studies have also revealed that prevertebral space invasion was an independent prognostic factor in patients with NPC that were treated by IMRT (4,16,17).…”
Section: Discussionmentioning
confidence: 93%